Pengendalian Turnover Intention pada Pegawai Kementerian X - Beny Agus Setiadi; R.N. Afsdy Saksono; Asropi Asropi (Universitas Negeri Surabaya, 2022)
This study aims to find the right controlling to controlturnover intention in employees at Ministry X. Thefocus is emphasized on how the organization as acareer place provides opportunities for employees tosurvive and advance the organization. This study uses aqualitative approach with data obtained from MinistryX participants purposely based on criteria that havemade a turnover, have a turnover intention, and arestaf managers. Data analysis is done by reducing,presenting, and drawing conclusions. The results of thisstudy indicate that the turnover intention factor tends tobe determined by the encouragement of internal factors.The internal factors that often arise are conveyed byparticipants, namely job satisfaction related toemployee career clarity and employee promotionopportunities. Controls that can be carried out are by1) Implementing internal rules regarding jobinformation so that there is no gap between positionqualifications and current employee competencies; and2) Making policies on employee career patterns andimplementing succession plans based on a merit system.Contributions in this study contribute to the control ofturnover intention in government institutions. Pergerakan organisasi ditentukan oleh adanya sumber daya manusia yang memiliki peran yang besar terhadap pencapaian kinerja organisasi secara keseluruhan sehingga sumber daya manusia dalam organisasi menjadi aset yang perlu untuk dipertahankan dan perlu pengelolaan jangka panjang. Penelitian ini dilakukan untuk mengetahui faktor turnover intention dan strategi pengendalian turnover intention di Kementerian X dengan metode penelitian kualitatif. Partisipan dalam penelitian ini adalah pegawai yang bekerja di kementerian X dan pegawai yang telah melakukan turnover di kementerian X. Hasil penelitian ini menunjukan bahwa faktor turnover intention cenderung ditentukan oleh faktor internal. Faktor internal yang muncul adalah kepuasan kerja yang berhubungan dengan kejelasan karier pegawai serta peluang promosi pegawai. Strategi pengendalian yang dapat dilakukan adalah dengan adanya Penerapan kebijakan dalam pengisian jabatan, peluang promosi dan kejelasan karier